Creation of songs to promote cultural tourism from the identity of folk performances in the Songkhla Lake Basin - Nilvanich, Korarit (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
Abstract The purpose of this research is to study the tourism promotion songs creation from local performing arts identities which appeared in the Songkhla Lake Basin area. This research conducted by qualitative research method. The research tools were 1) the unstructured observation for collecting the area general information 2) The local people interview about the opinions and suggestions for the creation songs 3) The evaluation form from the experts. The research found that there were 9 creation songs which were the best of Muang Korn Volume 1,2,3 Song art Songkhla town, Songkhla charming, Songkhla art way, Nora Uncle City And the people of Uncle City.Three of these songs described about way of life, costumes and food. Another three songs were about arts, craft works, sculptures, paintings and carve works. The last three songs expressed music, theatre and movies. The creation and arrangement of those songs inspired from the music identities of local performing arts which were shadow puppets (Nang Talung), Manora and Likay Hulu mixed up with contemporary music. Moreover, the songs were created from local people suggestions and evaluated by the music experts. Those songs were broadcasting on various medias to promote the cultural tourism and using in related activities in Songkhla Lake Basin area. Keywords: Cultural Tourism, The song creation, Songkhla Lake Basin